(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Coomans, A. *2006. Book review: ARSSEN, G. 2006. Life and work of Dr. Johannes Govertus de Man (1850-1930). A Crustacea and Nematoda specialist. Koninklijke Brill N.V. Leiden, The Netherlands. 119 pp + CD [ISBN-10: 90 0414 9694, ISBN-13: 978 90 0414 969 4